Walter Hines Page : ambassador to the Court of St. James's - Gregory, Ross (University Press of Kentucky, 1970)
This lucid study assesses Page's career as ambassador to Great Britain from 1913 to 1918. It reconsiders the famous publisher's impact on American diplomacy through an examination of British-American relations in that troubled period. Page, a friend of Woodrow Wilson and an intense Anglophile, devoted his major efforts to bringing the United States into the war on the side of the Allies and to cementing Anglo-American friendship. The book brings to bear information from all pertinent manuscript collections in the United States and introduces new information on British-American relations from re.